Africa Digest : Trends and issues in macro environment Vol. 3 - Burger, Johan (2020)
The Africa Digest is a fortnightly e-newsletter scanning the key trends in the macro-environment and industry to promote knowledge and raise understanding of business in Africa. This issue explores housing infrastructure, mini-grids, oils and gas industry, regional integration and technology in Africa.